A novel, simple 3D/2D outflow boundary model for blood flow simulations in compliant arteries. (30th September 2018) - Attaran, Seyed Hamidreza; Niroomand-oscuii, Hanieh; Ghalichi, Farzan
Highlights: A novel outflow boundary model is presented which is suitable for FSI simulation of blood flow in arteries. This model can be easily implemented in commercially available software packages without significant complication. Our model is capable of capturing the three main features of downstream: resistance, compliance and wave reflection. The validity of our model is tested in a simulation of axisymmetric model of aorta. Abstract: Outflow boundary condition is one of the most challenging issues in the simulation of blood flow in arteries. It has a great impact on the solution within computational domain. Our aim in the present study is to develop a new outflow boundary model which can be easily implemented in commercially available software packages and capable of capturing the three main features of downstream: resistance, compliance and wave reflection. The new boundary model is an extension of a 2D/3D elastic tube to the end of the main computational domain which is partially filled with porous material. Wave reflection characteristics of our model are investigated by applying it to the end of a straight vessel and an axisymmetric model of an aorta. The sensibility of the solution to model parameters is also studied. Pressure, velocity, and wave intensity curves resulted from numerical simulations, are presented. All main characteristics of pressure and flow waves were observed in results of simulations with our boundary model. Computed pressures were in agreement with those previously published in the literature. It is shown that this model provides accurate results while it avoids complexities of other models such as Windkessel and structured tree.